Participant Perspectives on Adapted Recreational Physical Activity Programs: The Nursing Home Model - Eda Gökçelik; Birol Çağatay Yaşar (Research in Sports Science, 2026)
The purpose of this study was to investigate the effects of active or passive recreational adapted physical activities on older adults. Accordingly, adapted physical activity programs and games were implemented with individuals defined within the older adult classification scale by the World Health Organization, and participants’ experiences and opinions were examined. A total of 13 older adults residing in nursing homes in İstanbul voluntarily participated in the study (female = 4, male = 9; age ≥ 64 years). The study was conducted in a nursing home selected through purposive sampling. The research consisted of three stages. First, recreation leaders and nursing home residents were informed about the study, and eligible individuals aged 64 years and above, with sufficient physical fitness and willingness to participate, were identified. Participants’ functional fitness levels were assessed by the institution’s physiotherapist, and individuals were considered eligible based on the absence of serious limitations in walking, balance, and basic mobility, as well as having no health-related barriers to participation in recreational adapted physical activities. In the second stage, participants were regularly involved in various adapted recreational physical activity sessions for eight weeks. In the final stage, semi-structured interviews were conducted to explore participants’ perceptions and experiences regarding the activities. This study was designed as a qualitative case study, utilizing in-depth one-on-one interview techniques. Semi-structured interview questions were employed as the primary data collection tool. The interviews were audio-recorded, and the data were analyzed using the qualitative analysis software MAXQDA 2020. As a result of the analysis, 12 codes emerged, which were grouped under five main themes: participation, motivation, perceived benefits, activity preference, and expectations. In conclusion, participation in recreational adapted physical activities plays a significant role in enhancing older adults’ motivation and overall experiences, contributing positively to both their physical and psychological well-being. Moreover, such programs serve as an important tool for improving quality of life in older individuals. These findings provide valuable insights for increasing physical activity participation among older adults and developing programs tailored to their specific needs. Cite this article as: Gökçelik, E., & Yaşar, B. Ç. (2026). Participant perspectives on adapted recreational physical activity programs: the nursing home model. Research in Sports Science, 16, 0071, doi: 10.5152/rss.2026.25071.